The nature of ammonium nitrate decomposition and explosions. Issue 4 (29th October 2020) - Willey, Ronald J.
Abstract: Ammonium nitrate explosions can cause significant destruction as shown with examples in West, Texas (2013) and Tianjin, China (2015). Yet, ammonium nitrate is available in nearly every garden center, and serves as one of the major fertilizers used throughout the world. Why is it safe to store in a garden center, and yet not safe when stored in wooden framed buildings? This presentation explores the nature of ammonium nitrate decomposition steps using a process simulator where adiabatic, constant pressure, and constant volume scenarios are evaluated. Answers are simple, yet complex. The first decomposition step is endothermic. In other words, there is a natural barrier that needs to be overcome before further decomposition. Further explanations are offered within the paper.